Coffee Wilt Disease 2010
DOI: 10.1079/9781845936419.0083
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic impact of coffee wilt disease.

Abstract: This chapter describes the severity and incidence of coffee wilt disease (Gibberella xylarioides) in East and Central Africa and discusses its impact on coffee production and productivity as well as its contribution to income, foreign currency, employment and livelihood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It has been estimated that the disease has cost $1 billion so far in terms of lost production and cost of management practices (Phiri and Baker 2009). Severe impacts on the incomes and livelihoods of coffee farmers in affected areas of DRC, Uganda, Ethiopia and Tanzania have been observed (Musebe et al 2009) and producers have had to diversify away from coffee production, either growing other crops or moving into nonagricultural activities.…”
Section: Coffee Wilt Disease (Cwd)mentioning
confidence: 98%
“…It has been estimated that the disease has cost $1 billion so far in terms of lost production and cost of management practices (Phiri and Baker 2009). Severe impacts on the incomes and livelihoods of coffee farmers in affected areas of DRC, Uganda, Ethiopia and Tanzania have been observed (Musebe et al 2009) and producers have had to diversify away from coffee production, either growing other crops or moving into nonagricultural activities.…”
Section: Coffee Wilt Disease (Cwd)mentioning
confidence: 98%
“…This disease could be a great concern for future sustainability of coffee production in Eastern and Central Africa and of major potential threat to the world coffee like that of the historical coffee leaf rust and coffee berry disease (Rutherford, 2006;Flood, 2009;Girma et al, 2009a). In Ethiopia, it is one of the major biotic factors constraining the crop production with rapid prevalence and severity in plantation, garden and semi-forest coffee systems (Girma et al, 2001(Girma et al, , 2009aGirma, 2004;Musebe et al, 2009). Recently, Sihen et al (2012) reported that coffee wilt is causing significant losses to coffee trees in the forest coffee systems of Ethiopia inhabiting invaluable gene pools of C. arabica.…”
Section: Introductionmentioning
confidence: 99%